Analisis Stilistika dalam Tunjuk Ajar Melayu karya Tenas Effendy - Rahayu, Sri; Alber, Alber; Basri, Hasan (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
Tunjuk Ajar Melayu (TAM) is very important for Malay people, especially in the past trying after all their power to disseminate, bequeath and perpetuate the teaching values ​​referred to through literature (both oral and written). Understanding and living a literary work, one of which is through the study of stylistics. Stylistics as one of the sub-sciences in literature plays a large role in the study of literature because it examines the way the writer uses elements and language rules by looking for the effects caused by the use of language, examining the characteristics of the use of language in literature. Stylistics studied the use of the figure of speeches in its function. In this study, the researcher formulated the research problems, what was the comparative and linkage figure of speeches in TAM by Tenas Effendy?. Therefore, this research was conducted to describe, analyze, and interpret the comparative and linkage figure of speeches contained in TAM by Tenas Effendy. This research used the content analysis method. The data was collected through documentation and hermeneutic techniques. The data was documented by reading, taking notes, then summarizing and grouping according to the type of work. The results of this study were comparative figure of speeches in TAM by Tenas Effendy consisting of simile, personification, metaphor, and allegory. The linkage figure of speech in TAM by Tenas Efendy consisted of synecdoche figure of speech of tutom pro parte category.